2021
DOI: 10.2337/db21-0587
|View full text |Cite
|
Sign up to set email alerts
|

Contraction-Mediated Glucose Transport in Skeletal Muscle Is Regulated by a Framework of AMPK, TBC1D1/4, and Rac1

Abstract: The two closely related RabGTPase-activating proteins (RabGAPs) TBC1D1 and TBC1D4, both substrates for AMPK, play important roles in exercise metabolism and contraction-dependent translocation of GLUT4 in skeletal muscle. However, the specific contribution of each RabGAP in contraction signaling is mostly unknown. In this study, we investigated the cooperative AMPK-RabGAP signaling axis in the metabolic response to exercise/contraction using a novel mouse model deficient in active skeletal muscle AMPK combined… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…AMPK activation occurs mainly through activation of the upstream liver kinase B1(kinase LKB1) through Thr172 phosphorylation of its catalytic domain in response to increased cellular AMP:ATP ratio ( Hawley et al, 2003 ; Woods et al, 2003 ). Activated AMPK inactivates its downstream target TBC1D1 ( Kramer et al, 2006 ; Treebak et al, 2006 ; Taylor et al, 2008 ; Ferrari et al, 2019 ; de Wendt et al, 2021 ) by phosphorylation (an interaction also known as “AMPK-TBC1D1 signaling nexus”; Chavez et al, 2008 ; Taylor et al, 2008 ; Vichaiwong et al, 2010 ; Treebak et al, 2014 ; Kjøbsted et al, 2016 ; Ferrari et al, 2019 ). TBC1D1 inactivation during exercise has been reported in mouse skeletal muscles ( Taylor et al, 2008 ; Vichaiwong et al, 2010 ; de Wendt et al, 2021 ) and in human skeletal muscles ( Jessen et al, 2011 ; Tobias et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMPK activation occurs mainly through activation of the upstream liver kinase B1(kinase LKB1) through Thr172 phosphorylation of its catalytic domain in response to increased cellular AMP:ATP ratio ( Hawley et al, 2003 ; Woods et al, 2003 ). Activated AMPK inactivates its downstream target TBC1D1 ( Kramer et al, 2006 ; Treebak et al, 2006 ; Taylor et al, 2008 ; Ferrari et al, 2019 ; de Wendt et al, 2021 ) by phosphorylation (an interaction also known as “AMPK-TBC1D1 signaling nexus”; Chavez et al, 2008 ; Taylor et al, 2008 ; Vichaiwong et al, 2010 ; Treebak et al, 2014 ; Kjøbsted et al, 2016 ; Ferrari et al, 2019 ). TBC1D1 inactivation during exercise has been reported in mouse skeletal muscles ( Taylor et al, 2008 ; Vichaiwong et al, 2010 ; de Wendt et al, 2021 ) and in human skeletal muscles ( Jessen et al, 2011 ; Tobias et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Activated AMPK inactivates its downstream target TBC1D1 ( Kramer et al, 2006 ; Treebak et al, 2006 ; Taylor et al, 2008 ; Ferrari et al, 2019 ; de Wendt et al, 2021 ) by phosphorylation (an interaction also known as “AMPK-TBC1D1 signaling nexus”; Chavez et al, 2008 ; Taylor et al, 2008 ; Vichaiwong et al, 2010 ; Treebak et al, 2014 ; Kjøbsted et al, 2016 ; Ferrari et al, 2019 ). TBC1D1 inactivation during exercise has been reported in mouse skeletal muscles ( Taylor et al, 2008 ; Vichaiwong et al, 2010 ; de Wendt et al, 2021 ) and in human skeletal muscles ( Jessen et al, 2011 ; Tobias et al, 2020 ). Activation of AMPK-TBC1D1 signaling nexus results in increased GLUT4 expression and translocation from the cytosol to the plasma membrane enabling increased glucose uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple upstream mechanisms including Rac1/actin and Ca 2+ /calmodulin-dependent protein kinase (CAMK) signaling are activated via muscle contraction [ 21 ]. These two signaling networks share downstream key proteins such as AMP-activated protein kinase (AMPK) and PI3K while also relying on novel targets such as TBC1D1/4 [ 22 , 23 ]. While GLUT4 is the most highly expressed glucose transport protein in skeletal muscle, there are other GLUT isoforms with physiological significance, notably GLUT1, which is constitutively present on the surface of skeletal muscle [ 24 ].…”
Section: Role Of Skeletal Muscle In Blood Glucose Regulationmentioning
confidence: 99%
“…Importantly, cytoskeletal rearrangements are critical events for insulin-stimulated glucose uptake in adipocytes and skeletal muscle. 41 Marcusohn reported that Rac1 does not participate in insulin signalling in adipocytes. 106 However, a recent finding of Balamatsias with co-workers 107 suggests that Rac1 is involved in glucose uptake in adipocytes.…”
Section: Mechanisms By Which the Rac1 Gene Polymorphisms May Contribu...mentioning
confidence: 99%